2024
DOI: 10.1177/01939459241236631
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship Between Nurse Fatigue, Alertness, and Medication Errors

Amany Farag,
Jacob Gallagher,
Lucas Carr

Abstract: Background: Working for extended hours in a physically and mentally demanding profession has subjected nurses to occupational fatigue. Limited evidence exists about nurse fatigue and alertness changes throughout shift work and their relationship with medication errors and near misses. Purpose: The purposes of this study were to: (1) assess the relationship between nurses’ fatigue and alertness, (2) evaluate nurses’ fatigue and alertness changes throughout their shift, and (3) examine the relationship between n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…With the rapid development of endoscopic diagnosis and treatment technology, the role functions and professional capabilities of endoscopic nurses are constantly increasing. Due to the complexity and particularity of the post, the occupational fatigue detection rate of endoscopic nurses reached 57.32%, which easily led to decreased work efficiency, increased risk of errors and accidents, and emotional exhaustion, affecting the quality of endoscopic diagnosis and treatment and patient safety ( 2 ). Research has found that sleep quality is one of the independent predictors of fatigue levels among nurses ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…With the rapid development of endoscopic diagnosis and treatment technology, the role functions and professional capabilities of endoscopic nurses are constantly increasing. Due to the complexity and particularity of the post, the occupational fatigue detection rate of endoscopic nurses reached 57.32%, which easily led to decreased work efficiency, increased risk of errors and accidents, and emotional exhaustion, affecting the quality of endoscopic diagnosis and treatment and patient safety ( 2 ). Research has found that sleep quality is one of the independent predictors of fatigue levels among nurses ( 3 ).…”
Section: Introductionmentioning
confidence: 99%